Diversity and distribution of fish fauna in the Ib River, a tributary of Mahanadi, India - Chandran, Rejani; Tyagi, L. K.; Jaiswar, A. K.; Raizada, Sudhir; Mandal, Sangeeta; Mayekar, Trivesh S.; Bisht, Amit Singh; Singh, Sanjay Kumar; Lakra, W. S. (Indian Journal of Fisheries, 2019)
Ichthyofaunal survey was conducted in the Ib River (21°44’ to 22°50’ N; 83°56’ to 83°54’ E), an important tributary of Mahanadi, to evaluate the diversity and distribution of freshwater fishes along six sites on seasonal basis between February, 2016 and January, 2017. A total of 55 species belonging to 42 genera, 21 families and 9 orders were recorded from the study area. Maximum number of species belonged to the Order Cypriniformes (41.8%) followed by Siluriformes (21.8%) and Perciformes (21.8%). Maximum value of species richness was observed in downstream areas; Sundargarh and Barghat and least in upper stretches of Pamsala. Shannon–Weiner diversity index ranged between 2.47 to 3.68 at the six sites of Ib River indicating healthy state of the river. Bray-Curtis similarity cluster analysis suggests that similarities between sites decrease with increasing distance, with highest similarity found between Sundargarh and Barghat sites. Baseline data on fish biodiversity has been generated in this study which can now be periodically monitored and form basis for future conservation plans.